The Level of Authentic Followership in Madurese Public Organizations - Utomo, Triyo (Universitas Muhammadiyah Sidoarjo, 2024)
Authentic followership is a research topic that is starting to be widely researched in the field of organizational behavior. This research aims to determine the level of authentic followership among members of public organizations in Madura. The method used is descriptive quantitative research. The scale used in this research is the authentic followership scale by Leroy. The participants in this research were 413 state civil servants who worked in various government agencies in Madura. The research results revealed that the majority of respondents (75%) were in the medium category. The remainder were classified as high (14%) and low (11%). These results can be used as a reference for further research discussing authentic followership.